The Need and Advantages of a National Bureau of Well-Log Statistics (071fd9b7-0e6e-4e78-af69-50c7c8800cc7) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1917)
ARTHUR KNAPP, Ardmore, Pa. (communication to the Secretary*). -The author has failed to consider the point which in my mind is the most convincing in advocating some sort of a bureau for the collection of well logs. I venture to say that 90 per cent. of the logs as taken today are absolutely worthless to any one but the one who has taken the log. This is largely due to the careless use of nomenclature. The author says on page 289, "He must ascertain which of the many factors might account for the dry hole in question and often only careful examination of well logs will convey this information." I believe that even a most careful examination of the average log reveals nothing. I have at hand a book on petroleum, by a well-known author. This book has a number of logs from fields all over the world, from which I shall illustrate. In a well log from Kansas I find "Soft gray shale" and in one from Humble I find "Hard blue shale." As a matter of fact the shale from Humble is softer than the shale from the Kansas well. The difference is that the drillers in Kansas, being used to limestone and